Canadian athletes' perspectives of mental health care and the importance of clinicians' sport knowledge: A multi-method investigation. (March 2021) - Jewett, Rachel; Kerr, Gretchen; Dionne, Michelle
Abstract: The purpose of this inquiry was to explore Canadian competitive athletes' perspectives on their mental health care experiences using a sequential multi-method design. The overarching aims of the study were to explore athletes' self-reported reasons for seeking mental health care, their awareness of their clinician's knowledge of sport, and the importance they placed on their clinician having knowledge of the sport context. A sequential mixed methods design was employed in which two studies were conducted to address these aims. In study one, 70 current and former Canadian athletes completed a short survey assessing basic demographics, athletes' reasons for seeking treatment, and the importance they placed on their clinician having sport knowledge for effective care. In study two, ten athletes participated in individual semi-structured interviews in which similar topics were explored. Fifty-six percent of surveyed athletes reported that their clinicians' knowledge of sport did not impact their treatment experience, however only 29% reported being aware of their clinician having such knowledge. Thematic analysis of the interview data suggested that the connectedness of athletes' mental health issues and sport participation played a role in the importance they placed on their clinician having sport knowledge. Key components of a successful therapeutic alliance included the clinician validating the importance of sport, normalizing athlete mental health challenges, and understanding the demands of the competitive sport culture. Conclusions of this inquiry include that assessing how inter-related an athlete perceives their mental health challenges and sport participation to be, and demonstrating an understanding of the importance of sport in competitive athletes' lives, are likely helpful strategies in working clinically with this population even if a clinician does not have specific experience with the sport context. Highlights: Clinician sport knowledge was relevant when mental health and sport were intertwined. Successful treatment was possible when providers did not have sport knowledge. Clinicians validating the importance of sport strengthened the therapeutic alliance. Clinicians should assess the role of psychological symptoms in sport functioning.